An indole diterpenoid isolated from the fungus Drechmeria sp. and its antimicrobial activity. Issue 19 (2nd October 2019) - Liang, Jia-Hao; Huo, Xiao-Kui; Cheng, Zhong-Bin; Sun, Cheng-Peng; Zhao, Jian-Chao; Kang, Xiao-Hui; Zhang, Tian-Yuan; Chen, Zhong-Jian; Yang, Tian-Mei; Wu, Ying-Ying; Deng, Xiao-Peng; Zhang, Yi-Xuan
Abstract: One new indole diterpenoid, drechmerin I (1 ), was isolated from the fermentation broth of Drechmeria sp. isolated from the root of Panax notoginseng . Its structure was elucidated based on 1 D and 2 D nuclear magnetic resonance (NMR), high resolution electrospray ionization mass spectrum (HRESIMS), and electronic circular dichroism (ECD) spectroscopic analyses as well as TD DFT calculations of ECD spectra. Drechmerin I (1 ) was assayed for its antimicrobial activity against Candida albicans, Staphylococcus aureus, Bacillus cereus, B. subtillis, Pseudomonas aeruginosa, and Klebsiella pneumonia, respectively. Drechmerin I (1 ) showed antimicrobial activities against B. subtillis with an MIC value of 200 μg/mL. The interaction of S. aureus peptide deformylase with drechmerin I (1 ) was investigated by molecular docking. Graphical Abstract: